DIETARY INTAKE, WORKLOAD, WORK FATIGUE AND STRESS LEVEL OF FEMALE WORKERS AT WOOD FACTORY IN EAST JAVA, INDONESIA - Dominikus Raditya Atmaka, S.Gz, MPH; Shintia Yunita Arini; Mawadhatul Khoiroh (Universitas Airlangga, 2025)
Introduction : Study in a Semarang factory showed 91% workers experience work fatigue and stress, which then increase the probability of work accidents. Work stress created by various factors and influence physical and psychological imbalances, which affect the emotions, thought processes, and conditions of a person being abused. Aims : This study aimed to examine the relationship between work stress and mental workload, work fatigue, and nutrient adequacy levels. Method : We used cross-sectional data of 120 female workers at “X” wood factory located in Lumajang, East Java, Indonesia. Assessment of mental workload, work fatigue, nutrient adequacy levels (energy, protein, and vitamin C), and work stress sequentially using NASA TLX (National Aeronautics and Space Administration Task Load Index) questionnaire, Questionnaire from the Industrial Fatigue Research Committee (IFRC), SQFFQ (Semi Quantitative Food Frequency Questionnaire), and a modified Questionnaire of the Management Standards and HSE Indicator Tool (HSE-MS IT). Results : The work stress of study participants 58.3% included in medium category, the nutritional adequacy was 50% normal category for energy, protein deficit 88.4%, and vitamin C deficit 80.0%. The level of work fatigue of respondents is moderate (48.3%) and high (1.7%). The percentage of respondent’s mental work is mostly included in high mental workload (63.3%). Workload (p=0.018) and protein adequacy (p=0.037) have correlation with work stress, while work fatigue (p=0.099), energy adequacy (p=0.117), and vitamin C adequacy (p=0.087) have no relationship. Conclusion : Work stress is related to mental workload, while work fatigue and levels of nutritional adequacy are not related.